A Nation of Laws, and Race Laws - Banks, Nina; Whatley, Warren C. (Journal of Economic Literature, 2022)
This article reviews the history of race laws in the United States as distinct from the rule of law, an idea found in the writing and speeches of Sadie Tanner Mossell Alexander, the first African American PhD in economics (1921). We review the race laws of slavery, lynching, Negro Jobs, and the making of the Black ghetto. We highlight the life and writings of Alexander and other early African American economists as an example of the cost of racial exclusion in the economics profession and how it has impeded the production of useful knowledge about the workings of the US economy. (JEL J15, K38, N31, N32, N41, N42)